Day 1 Wed, August 24, 2016 2016
DOI: 10.2118/181861-ms
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Hydraulic Fracturing Fluid: Field Deployment and Performance Evaluation in Saudi Arabia's Tight Gas Reservoirs

Abstract: With the increase in demand for energy, natural gas from tight reservoirs is being targeted abundantly around the globe by different operators using hydraulic fracture technology. Reducing the environmental footprint associated with hydraulic fracturing is a priority in optimizing this technology. An environment friendly, polymer-free fracturing fluid has shown remarkably consistent results, following multiple deployments in Saudi Arabian tight gas formations. Alongside laboratory tests, field s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Technologically, hydraulic fracturing is associated with the circulation of a large amount of a mixture of water, chemicals, surfactants and sand [9]. Therefore, near the deposits there is a significant accumulation of waste water contaminated with chemicals, which can get into the soil, destroying its fertile properties and groundwater.…”
Section: Methodsmentioning
confidence: 99%
“…Technologically, hydraulic fracturing is associated with the circulation of a large amount of a mixture of water, chemicals, surfactants and sand [9]. Therefore, near the deposits there is a significant accumulation of waste water contaminated with chemicals, which can get into the soil, destroying its fertile properties and groundwater.…”
Section: Methodsmentioning
confidence: 99%
“…The main drawbacks of HCl are corrosive due to its high reactivity and shallow penetration into the formation. HCl-based acids, such as gelled, emulsified, and viscoelastic (VES), were also examined in which they provided a better performance with some drawbacks such as the filter cake damage, high frictional losses, and longer mixing time. , Anderson and Fredrickson found that fracture conductivity is also affected by the flow regime and the dissolution volume. The contact time between the acid and rock could play a role in generating good conductive pathways, but it is dependent on the acid and formation type.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were conducted to optimize the efficiency of acid fracturing treatments, and experimental and simulation approaches were used. Different types of acids were examined, including straight, gelled, and emulsified acids. The most common acid is HCl, which can dissolve different types of carbonate rocks and induce rough fracture surfaces. However, several problems are associated with straight HCl acid injection, such as corrosion due to the high reaction rate and short penetration within the fracture. , The HCl acid can be retarded in acid fracturing treatments by adding viscoelastic surfactants (VES), emulsifiers, gelling agents, and cross-linkers.…”
Section: Introductionmentioning
confidence: 99%